PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM DI MAN REJOSO DARUL ULUM JOMBANG - Tri Darmawan Supanda; Muhammad Hanif; Lia Nur Atiqoh Bela Dina (VICRATINA, 2019)
The aim of the researchers was 1) to describe the quality of Islamic education in MAN Rejoso Darul Ulum Jombang. 2) describe the role of the principal in improving the quality of Islamic education in MAN Rejoso Darul Ulum Jombang. To get the results of the study, researchers used a qualitative approach with the basis of phenomenological thinking and the type of case study research, data collection techniques through observation, interviews, and documentation. The results of the research show that, 1) the quality of Islamic education in MAN Rejoso Darul Ulum Jombang has increasingly increased. This can be seen from the habituation and programs that have been designed starting from the activities of the Ministry of Religion or Ministry Of Religion, activities that are formed from Islamic boarding schools because the notes of students in the MAN Darul Ulum school are domiciled in boarding school and become the flagship program of the Qur'an. In addition, there are also many achievements in the field of religion, both academic and non-academic. 2) the role of the school principal in improving the quality of Islamic education, namely to request activities effectively and efficiently. Providing coaches for extras or teachers with training, seminars, workshops and training, collaborating with other agencies, adding religious subjects into intensive hours following PIB conducted in class XI and providing programs and religious practices to all students for example the Dhuha prayer, dzhur congregation, istighosah, reciting the yellow book, aqidatul lay and so on. Discipline students to carry out habituation and provide the widest possible forum for students who want to be creative.